The prevalence of the genus Eimeria in Draught and Al- Fourosia club horses of Baghdad Province: Athmar K. Abbas, Dalia Ahmed Kalef and Amer Rasool Fadhl - Kalef, Dalia Ahmed (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of the study was to investigate the prevalence of infection with the genus Eimeria in draught and Al- Fourosia club horses of Baghdad province regarding season sex, and age. The prevalence of Eimeria oocysts was investigated from November 2009 to July 2010 in 369 horses from Baghdad province; they included 136 draught horses and 233 Al-Fourosia club horses varying in age from < 2-12 years old. Fecal samples were examined by using direct method and flotation technique. Eimeria oocysts were found in 75 (20.32%) of the samples divided into 41(30.14%) from draught horses and 34 (14.59%) from Al-Fourosia club horses with a significant difference (P<0.05) between the two groups. No differences were recorded regarding sex. The highest rate of prevalence was recorded in draught horses during April, May and June, and the lowest rate, in January and July. In Al-Fourosia club horses the rate of prevalence was also highest in April, May and June, while the lowest rate, was in January and December. The results showed the effect of the age on the rate of prevalence with significant differences (P<0.05) between draught horses and Al- Fourosia club horses at less than 2 years old; the rate was 0% in draught horses and 11.11% in Al- Fourosia club horses. In contrast, the rate was much higher in drought horses than Al- Fourosia club horses at the age of 2-4 years old. A similar finding was recorded in the 4-6 year old group.